Degradation of fluorene and phenanthrene in PAHs-contaminated soil using Pseudomonas and Bacillus strains isolated from oil spill sites. (15th February 2019) - Rabodonirina, S.; Rasolomampianina, R.; Krier, F.; Drider, D.; Merhaby, D.; Net, S.; Ouddane, B.
Abstract: Biodegradation of 3-ring and 4-ring polycyclic aromatic hydrocarbons (PAHs) model (fluorene, phenanthrene, fluoranthene and pyrene) were investigated. Twenty-seven bacterial strains were isolated from contaminated-site by oil spills. PAHs-degrading bacteria were screened to select high tolerant species for ensuring an efficient bioremediation. Each of the isolated bacterial strains was grown under different PAHs concentrations (250, 500, 1000 and 1500 mg/L). Among the 27 strains, 8 resulted to be resistant to high concentration level of PAHs (1500 mg/L) and thereof can use PAHs as sole source of carbon and energy. The most tolerant strains were molecularly identified using mass spectrometer MALDI-TOF VITEK MS and 16S rDNA sequencing approaches. The identified bacterial strains Pseudomonas stutzeri ( P. stutzeri ), Bacillus simplex ( B. simplex ) and Bacillus pumilus ( B. pumilus ) were used for the bioremediation experiment of soils contaminated by PAHs. The studies were conducted under controlled conditions using soil spiked with a mixture of the target PAHs and the three microcosm strains. The results revealed that only fluorene and phenanthrene, which are low molecular weight PAHs, were degraded efficiently within 72 days of test organism incubation. These degradations were about 65–86% and 86–95% for fluorene and phenanthrene, respectively. At the same time and conversely to fluorene and phenanthrene, the high molecular weight PAHs, pyrene and fluoranthene were recalcitrant to these selected microbial strains. The biodegradation kinetics of both fluorene and phenanthrene were fit a first order rate with R 2 values ranging from 0.88 to 0.92. The half-lives of phenanthrene (2.4–2.7 days) and those of fluorene (3.5–4.6 days) were all less than 10 days, delineating therefore acclimatization with the strains. Graphical abstract: Image 1 Highlights: Polycyclic Aromatic Hydrocarbons (PAHs) biodegradation. PAHs contaminated soil Bioremediation. Bacterial PAHs degradation by a select high tolerant species in Contaminated soil. Molecular identification of tolerant strains by mass spectrometer MALDI-TOF. Pseudomonas and Bacillus strains isolated from soil.